Novel Coronavirus Disease (COVID-19): Social Distancing, Isolation and Quarantine are Key Success Factors of Nepal’s Public Health Practices or Something Else? - Pathak, K.P.; Gaire, T.; Acharya, D. (Kathmandu University Medical Journal, 2020)
Novel Coronavirus Disease (COVID-19) is an infectious disease similar form of pneumonia/ SARS-CoV-2- impacting deadly globally. The main objective of this article is to analyze the studies and gather of the current information aimed at COVID-19 and analyze the situation of Nepal. We summarized the published articles from the web pages, Journals, Google search engine. It is declared as a public health emergency. However, why COVID-19 does not register in developing counties (Nepal) rather than China, Europe and North America it is unknown. Nepal has lower experiences of the COVID-19 where only 49 death cases registered and total cases 19,237 cases throughout the country (till 08/1/2020). Nepalese health services need to maintain up than today and follow lockdown, isolation, social distance and an advance screening test kit around the country.